2020
DOI: 10.3389/fnbeh.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

Mating Enhances Expression of Hormonal and Trophic Factors in the Midbrain of Female Rats

Abstract: Among female rats, mating enhances neurosteroid formation in the midbrain ventral tegmental area (VTA; independent of peripheral steroid-secreting glands, ovaries, and adrenals). The sources/targets for these actions are not well understood. In Experiment 1, proestrous rats engaged in a mating paradigm, or did not, and the midbrains had been assessed via the Affymetrix rat genome microarrays. In Experiment 2, the influence of gonadal and adrenal glands on the expression of these genes was assessed in rats that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…Evidence in a study of the role of hormones in sports reported that the catecholamine hormone stimulates the occurrence of lipolysis by stimulating β-adrenal receptors which occur when exercising physical activity (Frye and Chittur 2020). In connection with the above, other researchers also found that the results of aerobic exercise have an effect on fat by stimulating the hormones that play an important role in reducing fat.…”
Section: Resultsmentioning
confidence: 93%
“…Evidence in a study of the role of hormones in sports reported that the catecholamine hormone stimulates the occurrence of lipolysis by stimulating β-adrenal receptors which occur when exercising physical activity (Frye and Chittur 2020). In connection with the above, other researchers also found that the results of aerobic exercise have an effect on fat by stimulating the hormones that play an important role in reducing fat.…”
Section: Resultsmentioning
confidence: 93%